Revisiting embryo assisted hatching approaches: a systematic review of the current protocols - Alteri, Alessandra (J Assist Reprod Genet, 2018)
Zona pellucida (ZP) manipulation, termed “assisted hatching” (AH), has been introduced in order to favor embryo hatching and ultimately improve assisted reproductive technology success but with poor proofs of safety and biological plausibility. We herein provide a systematic review of clinical outcomes following the application of different methods of ZP manipulation on fresh or frozen/thawed embryos at different developmental stages in different groups of patients. Out of the 69 papers that compared the clinical outcomes deriving from hatched versus non-hatched embryos, only 11 considered blastocysts while the rest referred to cleavage stage embryos. The ZP thinning of fresh embryos either by chemical or laser approach was shown to provide very limited benefit in terms of clinical outcomes. Better results were observed with procedures implying a higher degree of zona manipulation, including zona removal. Studies comparing the mechanical or chemical procedures to those laser-mediated consistently reported a superiority of the latter ones over the former. Literature is consistent for a benefit of ZP breaching in thawed blastocysts. This review provides the current knowledge on the AH procedure in order to improve its efficacy in the appropriate context. Embryologists might benefit from the approaches presented herein in order to improve Assisted Reproduction Technologies (ART) outcomes.